The greater journey : Americans in Paris, 1830-1900 - McCullough, David G. (Simon & Schuster, 2011)
McCullough mixes famous and obscure names and delivers capsule biographies of everyone to produce a colorful parade of educated, Victorian-era American travelers and their life-changing experiences in Paris.